Analysis of Gross Profit Margin on Changes in Sales and Cost of Goods Sold on CV Rijiki Advertising Tolitoli: ANALISIS MARGIN LABA KOTOR ATAS PERUBAHAN PENJUALAN DAN HARGA POKOK PENJUALAN PADA CV RIJIKI ADVERTISING TOLITOLI - Nahdatussa’dah Nahdatussa’dah; Edi Yanto (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to find out and analyze changes in CV gross profit. Rijiki Advertising Tolitoli which is reviewed in terms of sales and cost of goods sold which affects gross profit in this study using a quantitative design. The data source is in the form of primary data, namely data obtained through interviews and documentation required and related to this research. The analysis method used is gross profit margin analysis. The conclusion obtained from this study is that the gross profit obtained by CV Rijiki Advertising in 2021 was IDR 144,924,373 or a gross profit margin of 37.28%, this gross profit was obtained from the gross profit of 3 products, namely billboards of IDR 83,627,425 and the gross profit of the data board of IDR 48,538,980 and the gross profit of the inauguration inscription of IDR 12,757,968 in 2022 increased to IDR 174,821,460 or a gross profit margin of 36.25% there has been an increase in sales volume The increase in selling price on the data board but when viewed from the Gross profit margin has decreased by 1.03%, while in 2023 there will be an increase in gross profit of Rp.20,057,898 due to the increase in selling price and gross profit margin cost of goods sold to 36.97%.